Iowa Urban FEWS: Integrating Social and Biophysical Models for Exploration of Urban Food, Energy, and Water Systems - Thompson, Jan; Ganapathysubramanian, Baskar; Chen, Wei; Dorneich, Michael; Gassman, Philip; Krejci, Caroline; Liebman, Matthew; Nair, Ajay; Passe, Ulrike; Schwab, Nicholas; Rosentrater, Kurt; Stone, Tiffanie; et al. (Frontiers in Big Data, 2021)
The majority of people in the world live in urban areas, and their high population densities, heavy reliance on external sources of food, energy, and water, and disproportionately large waste production result in severe and cumulative negative environmental effects. Integrated study of urban areas requires a system-of-systems analytical framework that includes modeling with social and biophysical data. We describe an urban food-energy-water systems (FEWS) analysis using an innovative co-simulation approach that allows assessment of current and prediction of future conditions, with an emphasis on local (urban and urban-adjacent) food production. This framework enables simultaneous analyses of climate dynamics, changes in land cover, built forms, energy use, and environmental outcomes associated with a set of drivers of system change related to policy, crop management, technology, social interaction, and market forces affecting food production. The goal of our work is to enhance understanding of the urban FEWS nexus so as to improve system function and management, increase resilience, and enhance sustainability. Our approach involves data-driven co-simulation to enable coupling of disparate food, energy and water simulation models across a range of spatial and temporal scales. These models will quantify energy use and water quality outcomes for current systems, and determine if undesirable environmental effects are decreased and local food supply is increased with different configurations of socioeconomic and biophysical factors in urban and urban-adjacent areas. The effort emphasizes use of open-source simulation models and expert knowledge to guide modeling for individual and combined systems in the urban FEWS nexus.